2018
DOI: 10.1109/tasc.2018.2808401
|View full text |Cite
|
Sign up to set email alerts
|

Demagnetization of Cubic Gd-Ba-Cu-O Bulk Superconductor by Crossed-Fields: Measurements and Three-Dimensional Modeling

Abstract: Superconducting bulks, acting as high-field permanent magnets, are promising for many applications. An important effect in bulk permanent magnets is crossed-field demagnetization, which can reduce the magnetic field in superconductors due to relatively small transverse fields. Crossedfield demagnetization has not been studied in sample shapes such as rectangular prisms or cubes. This contribution presents a study based on both 3D numerical modelling and experiments. We study a cubic Gd-Ba-Cu-O bulk superconduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…In our stack, the penetration front contains both the penetrates from the top and bottom of each individual tape. This is the same qualitative behavior found for superconducting bulks [30]. The oscillations in the current profiles in figure 10(e,f) are due to numerical error.…”
Section: Trapped Magnetic Field In the Stack Of Tapessupporting
confidence: 81%
See 1 more Smart Citation
“…In our stack, the penetration front contains both the penetrates from the top and bottom of each individual tape. This is the same qualitative behavior found for superconducting bulks [30]. The oscillations in the current profiles in figure 10(e,f) are due to numerical error.…”
Section: Trapped Magnetic Field In the Stack Of Tapessupporting
confidence: 81%
“…A more detailed trapped field profile is calculated along the (red) line B t above the sample on figure 13 (a). The profile has the usual symmetric peak at the end of the relaxation time shift, contrary to cubic bulk samples [30]. The cause of this difference is the thin film shape of tapes, as follows.…”
Section: Trapped Magnetic Field In the Stack Of Tapesmentioning
confidence: 94%
“…Appearance of a significant z component of j , necessary for shielding the zero-field core, is an unexpected feature of current density distribution discovered and explained in [16][17][18]. We found that smoothing, employed in the FFT-based method, smears the narrow peaks of z j and, therefore, had to use a weaker Gaussian filter with 0.5d   to arrive at the z j -distribution ( Figure 6) similar to that in [19].…”
Section: Bulk Magnetization: Simulation Resultsmentioning
confidence: 99%
“…Althgough, uncoupled stacks (and coils) and fully coupled stacks have been well studied by many researchers before, the case of an intermediate finite resistance ("partial coupling") has not been previously studied for stacks of tapes. Previous studes focused on ac loss under perpendicular magnetic field [19][20][21][22][23][24][25][26][27], ac loss under transport current [28][29][30][31][32], ac loss with consideration of ferromagnetic material [33][34][35][36], dynamic resistance under various applied field [37][38][39][40], magnetization and decay of trapped magnetic field [41][42][43][44][45][46][47][48], multifilamentary calculations [19,49], among other topics. Thanks to the presented numerical 2D MEMEP model, this article systematically studies and discusses the amplitude-dependence, frequency-dependence, and resistance-dependence of coupling loss under parallel magnetic field.…”
Section: Introductionmentioning
confidence: 99%